A Survey on the Physical Condition of Pencak Silat Athletes of the Persaudaraan Setia Hati Terate Sleman Branch in 2025 - Ari Ortega; Ipang Setiawan (Universitas Negeri Semarang, 2025)
This research aims to identify and describe the physical condition level of pencak silat athletes from the Persaudaraan Setia Hati Terate (PSHT) Sleman Branch in 2025. Specifically, this study measures the dominant physical components in pencak silat, namely: muscle strength, endurance, speed, agility, flexibility, and explosive power. This study is a quantitative descriptive research using a survey method with tests and measurements. The sample consists of all active athletes training at the PSHT Sleman Branch training center, selected using a total sampling technique. The instruments used include (1) the Push-up Test for strength; (2) the Beep Test for endurance; (3) the 30-meter Sprint for speed; (4) the Side Step Test for agility; (5) the Sit and Reach Test for flexibility; and (6) the Standing Jump Board for explosive power. The collected data were analyzed using descriptive percentage statistics to be classified into categories (Very Good, Good, Average, Poor, Very Poor). The results indicate that the physical condition of the PSHT Sleman Branch pencak silat athletes is at a moderate or “average” level, with a total average score of 20 points for both male and female athletes. In detail, female athletes performed best in speed, agility, and flexibility; had average performance in strength and explosive power; and were lacking in endurance. Meanwhile, male athletes excelled in speed, strength, and power; had average performance in agility and flexibility; and were also lacking in endurance. In conclusion, several training programs are recommended to improve the less-than-optimal components. These include High-Intensity Interval Training (HIIT), Fartlek running, and circuit training to enhance endurance; plyometrics and weightlifting for strength and power; and agility ladder drills and dynamic stretching programs to improve the athletes’ flexibility and agility.